THE EXTRACTS OF PACIFIC OYSTER (CRASSOSTREA GIGAS) ALLEVIATE OVARIAN FUNCTIONAL DISORDERS OF FEMALE RATS WITH EXPOSURE TO BISPHENOL A THROUGH DECREASING FSHR EXPRESSION IN OVARIAN TISSUES - Zhou, Jue; Qu, Fan; Jin, Yue; Yang, Dong-Xia (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Bisphenol-A (BPA) is one of the widespread industrial compounds, which has adverse effects on animal and human health. The study was aimed to explore the effects of Crassostrea gigas extracts (CGE) in alleviating ovarian functional disorders of female rats with exposure to BPA and the underlying possible mechanism. Materials and methods: Eighteen four-week-old female Sprague-Dawley (SD) rats were randomly divided into BPA group (50mg/kg BPA), BPA+CGE group (50mg/kg BPA+50mg/kg CGE), and control group (equivalent dosage of vehicle) with 6 rats in each group. After a 6-week treatment ended, the serum levels of estradiol (E2), follicle stimulating hormone (FSH), luteinizing hormone (LH) were measured by using commercial standard assay kits. The expression levels of FSH receptor (FSHR) in the rat ovarian tissues were respectively detected by immunohistochemistry and Real-time PCR. Results: CGE treatment markedly increased E2 levels and decreased FSH levels in the serum (P<0.05), however, the alterations of serum LH levels were not significant (P>0.05). The protein and mRNA expression levels of FSHR were the lowest in the ovaries of control rats and the highest in BPA rats (P<0.05). CGE treatment markedly decreased the expression levels of FSHR in the ovarian tissues (P<0.05). Conclusions: Crassostrea gigas successfully alleviates ovarian functional disorders of female rats with exposure to BPA partly through decreasing FSHR expression levels in the ovarian tissues.